Is there an optimal prostate-specific antigen threshold for prostate biopsy?. Issue 8 (August 2011) - Stephan, Carsten; Miller, Kurt; Jung, Klaus
Prostate-specific antigen (PSA) remains the best biomarker available for early prostate cancer (PCa) detection. Increasing PSA values are associated with increasing PCa risk. The traditional PSA cut-off of 4 µg/l was lowered because the PCa detection rates are similar in the PSA ranges 2–4 and 4–10 µg/l. This approach increases sensitivity, but also lets the numbers of 'insignificant cancers'' rise. Thus far, the used PSA cut-offs 2.5, 3 or 4 µg/l provide a reasonable balance between excessive detection rates and the risk of missing relevant PCa. Specificity of PSA has been enhanced by using PSA derivatives, PSA isoforms, new biomarkers and multivariate models. PSA should be used intelligently and several other factors should be considered for a final biopsy decision.